Analisa Percepatan Produktifitas Akibat CCO (Contract Change Order) Studi Kasus Pada Pekerjaan Pembangunan Apron Baru Bandara SSK II, Pekanbaru - Rasyid, Yusuf; Taufik, Hendra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This research discuses about productivity performance for construction of new apron that effect of additional volume in the Contract Change Order and discuses about treatment of project performance acceleration with overtime method, additional resources method, and shift time method that measureable to minimum cost performance till the time schedule planning completely and without disadvantage cost. This research intend to handling most of airport construction matter especially for additional volume matte that effect to productivity decreased that performance delay potentially or additional project time schedule. According of this research implementation of additional resources with shift time can rise productivity everyday without additional extra time. Additional resources with shift time that have minimum cost performance cost, therefor construction of new apron will done on schedule completely with the minimum cost performance.Keyword: Acceleration Productivity, Production Cost, Airport Project,Apron, Overtime, Shift Time, Additional Sources.